Using a Financial Calculator to Make Financial Decisions - Josephine Turner (EDIS, 2004)
Many financial problems can be solved quickly and easily using a financial calculator. Although calculations involving compound interest, periodic payments, and declining or increasing balances are complex, a financial calculator makes them simple. Regardless of your mathematical skills and training, you can make such calculations quickly and easily. This publication shows you how. This document is FCS5263/FY442, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, UF/IFAS, Gainesville, FL 32611. First published: July 2003.